THE INFLUENCE OF GROWTH OPPORTUNITIES, CAPITAL STRUCTURE, PROFITABILITY, AND DIVIDEND POLICY ON FIRM VALUE (In Pharmaceutical Companies Listed on the Indonesia Stock Exchange 2014-2022) - Lilin Marsiati; Pristin Prima Sari; Ratih Kusumawardhani (Published by the Faculty of Economics and Business, University of Labuhanbatu, North Sumat, 2024)
This research aims to see the influence of growth opportunities, capital structure, profitability and dividend policy on company value. The type and source of research data is quantitative data using financial reports on pharmaceutical companies listed on the IDX for 2014-2022, while the sampling technique uses purposive sampling to obtain 9 pharmaceutical companies that meet the criteria. The method used in this research is multiple linear regression analysis, using the SPSS program to test it. The results show that partially growth opportunities (PER) and profitability (ROA) have a positive and significant effect on company value. Capital Structure (DER) has a negative but significant effect on company value. Dividend Policy (DPR) has a negative and insignificant effect on company value. Meanwhile, simultaneously the results of the F test and the coefficient of determination test show that X1, X2, X3, and X4 have a simultaneous effect on Y.